Towards A Sustainable Financial Future: Exploring The Influence Of E-wallet Adoption Among Gen Z In Malaysia - Nurul Atasha Jamaludin; Hafizah Omar Zaki; Raudha Md. Ramli; Suhaida Herni Suffarruddin (Faculty of Business and Economics Universiti Malaya, 2024)
Indexed by Scopus